2021
DOI: 10.1002/adfm.202100848
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Cell Microenvironment: Hydrogel‐Based Strategy for Recapitulating Dynamic ECM Mechanics

Abstract: The native extracellular matrix (ECM) generally exhibits dynamic mechanical properties and displays time‐dependent responses to deformation or mechanical loading, in terms of viscoelastic behaviors (e.g., stress relaxation and creep). Viscoelasticity of the ECM plays a critical role in development, homeostasis, and tissue regeneration, and its implication in disease progression has also been recognized recently. Hydrogels with tunable viscoelastic properties hold a great promise to recapitulate such time‐depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
122
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 256 publications
0
122
0
Order By: Relevance
“…Hydrogel, a crosslinked hydrophilic polymer that possess similar structural network and water content with ECM, can be designed with specific viscoelasticity that toward target tissues for controlling the cellular behaviors [ 42 ]. Different crosslinking mechanisms (e.g., physical interactions, supramolecular interaction and dynamic covalent interactions) for synthesizing viscoelastic hydrogels and the underlying mechanobiology mechanisms have been reviewed elsewhere [ 43 ]. Here we will highlight the influence of dynamically mechanical microenvironment created by various viscoelastic hydrogels, including supramolecular networks, interpenetrating network (IPN) and dynamic bonds formed networks, on the fate of MSCs in the osteochondral restore and regeneration.…”
Section: Guiding Mscs Fate Via Viscoelastic Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogel, a crosslinked hydrophilic polymer that possess similar structural network and water content with ECM, can be designed with specific viscoelasticity that toward target tissues for controlling the cellular behaviors [ 42 ]. Different crosslinking mechanisms (e.g., physical interactions, supramolecular interaction and dynamic covalent interactions) for synthesizing viscoelastic hydrogels and the underlying mechanobiology mechanisms have been reviewed elsewhere [ 43 ]. Here we will highlight the influence of dynamically mechanical microenvironment created by various viscoelastic hydrogels, including supramolecular networks, interpenetrating network (IPN) and dynamic bonds formed networks, on the fate of MSCs in the osteochondral restore and regeneration.…”
Section: Guiding Mscs Fate Via Viscoelastic Biomaterialsmentioning
confidence: 99%
“…They found that highly adaptive linking improved cellular structures (proliferation, ECM deposition, et al), but slowly relaxed cross-linking was also required to achieve high quality new cartilage tissue [ 51 , 52 ]. Besides the temporally evolving properties capable of directing cell behavior provided from dynamic materials, dynamic covalent hydrogels also enhance stem cell therapy for cartilage regeneration including as minimally invasive injectable cell delivery vehicles, bioinks for 3D printing [ 43 ]. To advance the field of dynamic covalent hydrogels and their application for cartilage tissue engineering, more research should focus on standardizing methods to characterize the viscoelastic properties, especially in presence of stem cells and in vivo condition.…”
Section: Guiding Mscs Fate Via Viscoelastic Biomaterialsmentioning
confidence: 99%
“…The time-dependent response of the native ECM to the action of stress is crucial for its interactions with cells. Indeed, the tensile forces of cells are used to remodel and reorganize the matrix to achieve spreading, proliferation and migration [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our efforts were motivated by observations that many cells spread more when cultured in three-dimensional (3D) hydrogels that are viscoelastic than in hydrogels that are elastic [7] , and that brain parenchyma is soft and viscoplastic [7-8] . We sought to develop a self-healing hydrogel with the low stiffness and fast stress relaxation of brain parenchyma, which could be injected into a brain lesion with in situ solidification (sol-gel transitions) with controllable material dispersion within the brain.…”
Section: Introductionmentioning
confidence: 99%